Effect of ultrasonic energy in washing of medical surgery gowns - GÜLTEKİN, BEKİR CENKKUT; YÜKSELOĞLU, SEVHAN MÜGE; CANOĞLU, SUAT (ELSEVIER SCIENCE BV, 2004)
Today, the use of medical textiles is very important for health and hygienic purposes. Although some of medical textile materials are disposable, surgery gowns are usually laundered and re-used. After the laundering it is desirable to have these gowns keeping some of their properties such as anti-microbial and tenacity properties. For this in mind, different surgery gowns were washed and compared. In this work, a special blend of polyester carbon anti-microbial and other surgery gowns were stained with blood and later washed with both conventional method and with ultrasonic energy. The results were also analysed spectrophotometrically and the tenacity of the fabrics were determined. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: surgery medical gowns; conventional washing; ultrasonic energy